Hubungan Kemandirian dengan Penyesuaian Diri pada Mahasiswa Perantau di Institut Agama Islam Tribakti (IAIT) Kediri - Nadya Khussotu Birliana; Ajeng Okvita Larasati (Journal of Theory and Practice in Islamic Guidance and Counseling, 2025)
We frequently encounter students who leave their homeland just to seek knowledge. Students who leave their area and only return home when their assignments are over. The findings and research problems in this study are: (1) the independence of study abroad students both in the cottage and in the boarding house. (2) self-adjustment of migrant students both in the cottage and in boarding houses. (3) the relationship between independence and self-adjustment in migrant students who are in the cottage and in boarding houses. This research is a quantitative research. The sample was 30 respondents from overseas students at the Tribakti Islamic Institute (IAIT) Kediri both in the cottage and in boarding houses. Collecting data using questionnaire method, documentation method and observation method. The data analysis technique used Kendall Tau Correlation with SPSS. From the results of the study, the magnitude of the correlation between independence and self-adjustment was 0.318 and the significance value was 0.016. The amount of correlation above shows that the relationship between independence and self-adjustment of overseas students at IAIT Kediri is categorized as a low positive relationship because the coefficient number is 0.318 with a low or weak positive relationship category.